Damage-Aid Alignment and Reconstruction Pace Diagnostics for Post-Earthquake Recovery - Evrim Oyguc; Resat Oyguc (Salehan Institute of Higher Education, 2026)
Post-earthquake reconstruction raises two governance questions that are rarely addressed jointly. Whether affected provinces receive allocations proportional to measured damage, and whether physical delivery keeps pace with official plans, remain open in the empirical literature. This study addresses both the 2023 Kahramanmaraş sequence, which affected eleven Turkish provinces and generated recovery needs of approximately USD 103.6 billion. Two rule-based diagnostics are specified, the Damage–Aid Alignment index, which combines Spearman rank correlation with Theil T divergence, and the Reconstruction Pace Index, a monthly delivery-to-plan rate governed by a pre-specified run rule. Both diagnostics operate on an author-compiled corpus of 15,928 building-level records aggregated to a province–month panel spanning March 2023 to August 2024 and cross-checked against independent remote-sensing products. A two-way fixed-effects panel regression complements the analysis. Alignment with need is strong, with a Spearman correlation of 0.836 and a Theil T of 0.087, though Hatay is over-allocated by 10.4 percentage points and Adıyaman is under-allocated by 6.0. Persistent pace shortfalls in three provinces are clear within two months and reflect mobilization frictions rather than systemic failure. The framework provides a low-friction, auditable pathway to routine post-disaster performance monitoring.